Strengthening Moral Values in Formation of Religious Attitudes of Elementary School Students Based on Thomas Lickona's Theory: Penguatan Nilai-Nilai Moral Dalam Pembentukan Sikap Religius Siswa Sekolah Dasar Berdasarkan Teori Thomas Lickona - Didik Didik; Supriyadi Supriyadi (Academia Open, 2022)
Strengthening Moral Values ​​in Formation of Religious Attitudes of Elementary School Students Based on Thomas Lickona's Theory, Thesis of Elementary School Teacher Education Study Program, Faculty of Psychology and Education, University of Muhammadiyah Sidoarjo, This study aims to determine how the concept of strengthening moral values ​​in attitude formation religion in elementary school students. In this study using qualitative research methods, research aimed at describing events, social activities, attitudes, beliefs, perceptions, thoughts of people individually or in groups to examine a state or condition of natural objects. While the type of research using literature study. namely a series of activities which relate to a method of collecting library data by reading and taking notes, as well as processing research materials. Based on the results of research using the type of literature study, it is stated that the existence of these moral values ​​is used as the basis for the formation of religious attitudes of elementary school students. Researchers have conducted research on strengthening moral values ​​in the formation of religious attitudes of elementary school students which resulted in the fact that the strengthening of moral values ​​can be used in the formation of students' religious attitudes. . The habituation method can be linked in learning and other activities. By refracting the strengthening of these moral values, students do every day so that they can form students' religious attitudes both in the school environment, family and community.